PENGKLONAN DAN PERUNUTAN NUKLEOTIDA GEN SELUBUNG PROTEIN DAN 3'UTR (untranslated region) PEANUT STRIPE VIRUS - Akin, Hasriadi Mat (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false FR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Cloning and sequencing of coat protein gene and 3’UTR (untranslated region) of peanut stripe virus. The cDNA of 3' terminal of peanut stripe virus genomic RNA was cloned and sequenced. The cDNA was ligated with plasmid vector pGEM-T Easy and transformed to competent cells of Escherichia coli. The 3' terminal of PstV genomic RNA contained 1195 nucleotides (nts). The region included the nucleotide sequences of NIb (nuclear inclusion body) (129 nts), CP gene (coat protein gene) (861 nts), and 3'UTR (untranslated region) (205 nts). The nucleotide sequence of a CP gene contained one long uninterrupted open reading frame (ORF) without a start codon, which ended a UAG stop codon. The 287 amino acid residues of PStV coat protein were predicted from the CP gene. The amino acid was analyzed for the presence of consensus polyprotein cleavage site for maturation of potyvirus polyprotein. A putative cleavage site was found at position 43 (Q/S) following the Valine (V) residue at -4 position. This isolate of PstV can be expected to be aphid transmissible because the coat protein contained a DAG triplet at position 53-55.